Unformatted text preview: f ( x ) g ( x ) ) = f ( x ) g ( x ) + f ( x ) g ( x ) (b) Use the product rule on the functions f ( x ) = 3 x and g ( x ) = x to ﬁnd the derivative of the functions f ( x ) g ( x ) = 3 x 2 . Note: Using methods other than the product rule to ﬁnd the derivative will receive no credit, but may be useful for checking your work. Solution: ( f ( x ) g ( x ) ) = (3 x * x ) = 3 x * 1 + x * 3 = 3 x + 3 x = 6 x...
View
Full Document
 Spring '08
 Smith
 Calculus, Derivative, Power Rule, Product Rule

Click to edit the document details